The Impact of the Psychological Contract on Academics. (April 2019) - Sewpersad, Romona; Ruggunan, Shaun; Adam, Jamila K.; Krishna, Suresh Babu Naidu
The purpose of this study is to qualitatively explore how new managerial practices have influenced the psychological contracts of academics at a university of technology. Little is qualitatively known about how new managerial policies shape psychological contracts for academics in higher education. This study adopts a generic qualitative approach that draws on an interpretivist paradigm. A sample of 15 academics was used. In-depth interviewing was the data collection method. Thematic analysis was employed to reduce the interview data into meaningful themes. Three main themes emerge from the interview data: (a) shifts in the nature of the employment relationship, (b) self-monitoring through performance management systems, and (b) the construction of students as clients. These themes also reflect the nuanced influence of new managerial practices on the psychological contract showing that there is a spectrum of positive and negative consequences. New managerialism policies do impact on psychological contract formation, but this can be positive (as a form of organizational learning) or negative (as a form of control and deprofessionalization). The challenge for managers is to design policy toward the positive side of the spectrum. There is limited qualitative work on psychological contracts and new managerialism in higher education, both at a national and international level. Extant work tends to emphasize negative consequences only of new managerial practices, while this study shows that the outcomes for psychological contracts are more complex than simple binary distinctions.